Navigating terragraphica : an exploration of the locations of identity construction in the transatlantic fiction of Ama Ata Aidoo, Paule Marshall and Caryl Phillips - Tait, Michelle Louise (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.